The forerunners and heirs of Origen’s Hexapla: the proceedings of the inaugural colloquium of the Phoenix Seminary Text & Canon Institute - Meade, John Daniel (De Septuaginta investigationes, 2024)
Although Origen and his Hexapla are well known among biblical scholars, questions about his philology, particularly textual criticism, persist. The Hexapla contained very important texts and translations of the Hebrew Scriptures, but unfortunately it was probably destroyed in the seventh century and we possess only fragments of it. This volume systematically treats the questions of Origen’s forerunners and heirs and attempts to reconstruct how Origen developed the philological method he received and also how his followers received and innovated his textual work.